The analysis of social appearance anxiety levels of physical education teacher candidates in terms of different variables - Metin Yuceant; Huseyin Unlu (Türk Spor ve Egzersiz Dergisi)
The purpose of this study is to examine the social appearance anxiety levels of physical education teacher candidates based on different variables. Participated in the current study 600 physical education teacher candidates studying at physical education and sports departments which were designed using a screening model. As a data collection tool, the Social Appearance Anxiety Scale was used in the study. In the data analysis process, as well as the descriptive statistics, a t-test for independent groups, one-way variance analysis, and Pearson correlation coefficient technique were used.The study results suggest that the social appearance anxiety levels of physical education teacher candidates were low. Although no meaningful relationship was found between the social appearance anxiety levels of physical education teacher candidates and their gender and income level variables, there was a significant difference based on their sports branches. Additionally, there was a meaningful difference found between age and social appearance anxiety levels of physical education teacher candidates.